High-Precision Interferometric Measurements of Gas Refractive Index Using Homodyne Detection - Yanan Miao; Fang Xie; Wentao Feng; Yifeng Zhu; Xun Zhang; Fang Liu (Sensors)
Balanced homodyne detection, which offers advantages that include low noise and strong anti-interference capabilities, is commonly used as a detection method in quantum metrology. In this article, we propose application of the balanced homodyne detection technique to the gas sensing and measurement field. By constructing a Mach–Zehnder interferometer based on balanced homodyne detection, we realize high-precision measurement of the refractive index of air. The device exhibits interference efficiency of 99% and a common-mode rejection ratio of 40 dB, thus enabling dynamic monitoring of optical phase changes. Under conditions that include a stabilized temperature of 25 °C, atmospheric pressure of 100.08 kPa, and relative humidity of 30%, the refractive index of air was measured experimentally to be <semantics>n=1.0002711</semantics> with a measured minimum standard deviation of <semantics>1×10−7</semantics>. The proposed technique provides high measurement sensitivity and stability, and it also offers the advantage of noncontact measurement. Furthermore, the proposed scheme is applicable to both measurement and dynamic sensing of the refractive indices of gases, along with sensing and measurement of transparent liquids and biological samples.